2019
DOI: 10.4103/jfmpc.jfmpc_611_19
|View full text |Cite
|
Sign up to set email alerts
|

Frenal attachment and its association with oral hygiene status among adolescents in Dakshina Kannada population: A cross-sectional study

Abstract: Background and Objective:Frenum is a mucous membrane fold that attaches the lip and the cheek to the alveolar mucosa, gingiva, and the underlying periosteum. The frena may jeopardize the gingival health when they are attached too closely to the gingival margin, either due to interference in the plaque control or due to muscle pull. Identifying labial frenum attachment and its association with oral hygiene helps in primary prevention of gingival health. The purpose of this study was to examine the prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 12 publications
8
10
0
Order By: Relevance
“…The distribution of frenal attachment types according to age showed that mucosal and gingival frenal types were noticed in patients aged between 13-15 y, while 12 years old children had a higher distribution of papillary frenal types. These results conformed with Divater et al, 2019;Zakirulla et al, 2021 and can be related to the tendency of the labial frenum to migrate more apically with aging (Pandiyan and Hedge, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The distribution of frenal attachment types according to age showed that mucosal and gingival frenal types were noticed in patients aged between 13-15 y, while 12 years old children had a higher distribution of papillary frenal types. These results conformed with Divater et al, 2019;Zakirulla et al, 2021 and can be related to the tendency of the labial frenum to migrate more apically with aging (Pandiyan and Hedge, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, the mean and SD of age among the participants was (13.85 ± 1.48) years which was in accordance with Rashid and Khalifa, 2021 and can be attributed to the age of eruption of maxillary permanent canine (Divater et al, 2019). Regarding the gender distribution, 50.7% of participants were females and 49.3% were males which were consistent with Khursheed et al, 2015 and can be attributed to females tend to seek dental treatment more than males (Hamasha et al, 2018;Songur et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations